1991
DOI: 10.1073/pnas.88.23.10500
|View full text |Cite
|
Sign up to set email alerts
|

p55CDC25 is a nuclear protein required for the initiation of mitosis in human cells.

Abstract: The cdc25+ gene of fission yeast encodes a phosphotyrosine phosphatase that dephosphorylates tyrosine-15 of p34CdC2 and thereby activates p34`2/cyclin to bring about entry into M phase. We have recently cloned a human homolog, CDC25, which rescues the M-phase initiation defect of yeast cdc25 temperature-sensitive mutants. Antibodies raised against the CDC25 gene product specifically recognize human proteins of -55 and -52 kDa. Micro'niection of affinity-purified anti-CDC25 antibodies into HeLa cells inhibits e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(147 citation statements)
references
References 28 publications
(40 reference statements)
6
141
0
Order By: Relevance
“…Among them, Cdc25 protein phosphatases are believed to be important regulators in control of cell cycle progression by activating cyclin-dependent kinases (Cdk) (Nilsson and Hoffman, 2000). Three Cdc25 homologs have been found in mammals, Cdc25A, Cdc25B, and Cdc25C (Sadhu et al, 1990;Millar et al, 1991;Nagata et al, 1991). Both Cdc25B and Cdc25C are thought to be regulators of G2/M transition through their ability to dephosphorylate and activate the Cdk1/cyclin B mitotic kinase complex, which is required for cell entry into mitosis (Nilsson and Hoffman, 2000) (Fig.…”
Section: Mechanisms Of Cell Growth Inhibition By K Vitamin Analogs Prmentioning
confidence: 99%
“…Among them, Cdc25 protein phosphatases are believed to be important regulators in control of cell cycle progression by activating cyclin-dependent kinases (Cdk) (Nilsson and Hoffman, 2000). Three Cdc25 homologs have been found in mammals, Cdc25A, Cdc25B, and Cdc25C (Sadhu et al, 1990;Millar et al, 1991;Nagata et al, 1991). Both Cdc25B and Cdc25C are thought to be regulators of G2/M transition through their ability to dephosphorylate and activate the Cdk1/cyclin B mitotic kinase complex, which is required for cell entry into mitosis (Nilsson and Hoffman, 2000) (Fig.…”
Section: Mechanisms Of Cell Growth Inhibition By K Vitamin Analogs Prmentioning
confidence: 99%
“…They are able to dephosphorylate both phosphoserines/threonines and phosphotyrosines on the same protein substrate. Cdc25B or Cdc25C regulate the transition from G 2 phase to mitosis through Cdk1 dephosphorylation (Millar et al, 1991;Strausfeld et al, 1994;Lammer et al, 1998). Cdc25A mainly activates Cdk2 and thereby induces progression from G 1 to S phase.…”
mentioning
confidence: 99%
“…Although all cdc25 genes rescue a S. pombe ts mutant, cdc25-22, they are supposed to have a different function in the cell cycle. For instance, the cdc25C protein is considered to be involved for the initiation of mitosis (Millar et al, 1991a) and the cdc25A protein is suggested to function after initiation of mitosis (Galaktionov and Beach, 1991). We chose the cdc25C as a possible cdc25 protein required for PCC induced by loss of RCC1 function.…”
Section: Introductionmentioning
confidence: 99%